Analysis and Optimization of a V-Shape Combined Pole Interior Permanent-Magnet Synchronous Machine With Temperature Rise and Demagnetization Considered - Mingqiao Wang; Haotian Zhu; Chengyu Zhou; Ping Zheng; Chengde Tong (IEEE Access, 2021)
Interior permanent-magnet synchronous machines (IPMSMs) have the advantages of high efficiency, high power density and outstanding flux-weakening ability, which make them widely adopted in electric vehicles (EVs). Conventional IPMSMs using rare-earth permanent magnet (PM) materials face the problems of instable price and irreversible demagnetization under extreme operating conditions. To overcome these shortcomings, a V-shape combined pole IPMSM (VCP-IPMSM) is proposed, in which NdFeB PMs at the outer ends of V-shape pole are replaced by ferrite PMs. The improvement of the magnetic-pole scheme on air-gap flux density is analyzed, and the influences of the magnetic-pole geometries on electromagnetic performance are investigated. The thermal circuit model of VCP-IPMSM is established, and the demagnetization characteristics of the machine at different temperatures are analyzed, by which the thermal and demagnetization constraints of magnetic pole are obtained. The genetic algorithm based on response surface models is applied to optimize the magnetic-pole cost and electromagnetic torque simultaneously. Accordingly, with thermal and demagnetization constraints integrated with the optimization method, an optimum scheme is obtained. In comparison with the conventional IPMSM with single-material pole, the proposed VCP-IPMSM is proved to be able to promote the air-gap flux density quality, improve the anti-demagnetization ability at high temperature, and decrease the rare-earth PM consumption with the output torque remaining unchanged.